Inventario y caracterización agronómica de especies y ecotipos de frutales nativos de la provincia de Loja - Guevara Robles, Darwin Manuel (2015)
The province of Loja is located in the southern region of Ecuador (Zone 7), with a surface area of 11730 km2 according to Mendieta (2012), and is home to a diversity of native fruit in the wild which is accepted and semi cultivated by the small and medium sized farmers. In this way they have been preserving them for their nutritional and medicinal use, regardless of the risks these native species run to planted crops as they expand on a large-scale and destroy the rest of the diverse native plant life. The value in conserving species of native fruit is that they adapt to the environmental conditions where they have been endured many years without any interference, so it is important to keep improving cultivation technology of both the domesticated and wild species, which must be preserved, because the small and medium sized farmers lack access to better-quality seeds due to high cost, thus becoming dependent on seed producing companies. A great many of the cantons of the province of Loja are being affected by deforestation and livestock, which affects the floristic diversity with the consequent loss of food fruit species such as a species of Tamarillo (Solanum cajanumense Kunth ), and others in a process of genetic erosion due to human actions. A classification of species of fruit was made in the 16 cantons of the province of Loja, taking into account the species and botanical family, climate, soil, topography and geographical conditions of each place, so that with the information obtained it was possible to draft a technical guide which consisted of native fruit; taxonomic description, habitat, practices and consumption patterns, thus focusing and evaluating the ancestral knowledge and know-how of the farmers. In this study it was possible to identify 41 species and 27 types of native fruit belonging to 19 botanical families, which are: Cherimoya Annona cheremola Mill; Guanabana Annona muricata L .; Chora Capparis millei Standl .; Piñuelos Aechmea magdalenae (André) André ex Baker .; Opuntia Tunilla quitensis F.A.C. Weber .; Tuna Opuntia ficus indica (L.) Mill .; Pitahaya Hylocereus polyrhizus (F.A.C.) Weber .; Soroca Cerus diffusus (Britton & Rose) Werderm.FAC; Toronche Vasconcela stipulata (Badillo VM) VM Badillo .; Chamburo Vasconcela pubescens A.DC .; Babaco Vasconcellea x heilbornii (Badillo VM) VM Badillo .; Joyapa Ceratostema sp .; Joyapa, Green Salapa Macleania rupestris (Kunth) AC Sm .; Guato Erythina edulis Triana ex Micheli .; Pacha luma Salacia sp .; Walnut, Juglans tocte NeTropica Diels .; Organic Avocado Persea americana L .; Guabo moss Inga striata Benth .; Hill Guabo fendleriana Benth .; Guabillo Inga sp .; Parakeet Guabo Inga sp .; Arrayan Myrcianthes halli (O. Berg) Mc Vaughn .; Saco agrio, saca Myrcia fallax (Rich.) DC .; Saco Myrcia bella Cambess .; Guava Psidium guajava L .; Guayabillo Psidium guineense Sw .; Granadilla Passiflora ligularis Juss .; Taxo Passiflora tripartita Juss.;Poir. ; Tumbo Passiflora quadrangularis L .; Passion Fruit Passiflora manicata (Juss) Pers;. Indindo, añalque Coccoloba sp .; Quique Hesperomeles obtusifolia (Pers) Lindl .; Blackberry Rubus alpinus Macfad .; Blackberry Rubus adenotrichos Schltdl .; Shiringo, Clambo Allophylus mollis (Kunth) Radlk .; Luma Pouteria lucuma (Ruiz & Pav.) Kuntze .; Tomatillo Solanum sp .; Pico Peak Acnistus arborescens (L.) Schltdl .; Tomatillo Solanum betaseum Benth .; Uvilla Physalis peruviana L .; Naranjilla Clavija euerganea Macbr Jf.